Open and Laparo-Endoscopic Repair of Incarcerated Abdominal Wall Hernias by the Use of Biological and Biosynthetic Meshes - Fortelny, René H.; Hofmann, Anna; May, Christopher; Köckerling, Ferdinand; , BioMesh Study Group (Frontiers in Surgery, 2016)
Introduction: Although recently published guidelines recommend against the use of synthetic non-absorbable materials in cases of potentially contaminated or contaminated surgical fields due to the increased risk of infection [1, 2], the use of bio-prosthetic meshes for abdominal wall or ventral hernia repair is still controversially discussed in such cases. Bio-prosthetic meshes have been recommended due to less susceptibility for infection and the decreased risk of subsequent mesh explantation. The purpose of this review is to elucidate if there are any indications for the use of biological and biosynthetic meshes in incarcerated abdominal wall hernias based on the recently published literature. Methods: A literature search of the Medline database using the PubMed search engine, using the keywords returned 486 articles up to June 2015. The full text of 486 articles was assessed and 13 relevant papers were identified including 5 retrospective case cohort studies, 2 case controlled studies, 6 case series. Results: The results of Franklin et al [23, 24, 25] included the highest number of biological mesh repairs (Surgisis®) by laparoscopic IPOM in infected fields which demonstrated a very low incidence of infection and recurrence (0,7% and 5,2%). Han et al [26] reported in his retrospective study the highest number of treated patients due to incarcerated hernias by open approach using acellular dermal matrix (ADM®) with very low rate of infection as well as recurrences (1,6% and 15,9). Both studies achieved acceptable outcome in a follow up of at least 3,5 years compared to the use of synthetic mesh in this high-risk population [3] Conclusion: Currently there is a very limited evidence for the use of biological and biosynthetic meshes in strangulated hernias in either open or laparo-endoscopic repair. Finally, there is an urgent need to start with randomized controlled comparative trials as well as to support registries with data to achieve more knowledge for tailored indication for the use of biological meshes.